Aspherical neighborhoods on arithmetic surfaces: the local case - Hübner, Katharina (Manuscripta mathematica, 2018)
On arithmetic surfaces over henselian discrete valuation rings we examine whether a geometric point has a basis of étale neighborhoods whose c-completed étale homotopy types are of type K(π,1) with respect to a full class c of finite groups.
Gesehen am 22.10.2018